Răspunsuri

2014-08-11T23:36:27+03:00
(a+b) : (a-b)= 2 rest 3

a+b= 2(a-b) +3

a+b =2a -2b +3

a-2a -3 = -2b -b

-a -3 = -3b  | -1

a +3 =3b

a= 3b+3

(a+b) =260 % din (a-b)

a+b= 260/100 * (a-b)

a+b= 26/10 * (a-b)

a+b= 13/5 * (a-b)

a+b =(13a-13b)/5

5a+5b =13a -13b

5a -13a = -13b -5b

-8a = -18b | -2

4a = 9b

a= 9b/4

a=3b+3

3b+3= 9b/4  aducem la acelasi numitor

12b +12 =9b

12b-9b = -12

3b = -12

b= -4

a= 9* (-4)/4=  9* (-1) = -9
1 5 1
Cel mai inteligent răspuns!
2014-08-12T00:10:04+03:00
(A + B) : (A - B) = 2 REST 3
A + B = 2(A - B) + 3
A + B = 2A - 2B + 3
-A = - 3 B + 3
A = 3 B - 3
A + B = 260/100(A - B)
A + B = 13/5 (A - B)
A + B = 13A/5 -13B/5 , ADUCEM LA ACELASI NUMITOR
5A + 5 B = 13 A -13 B
- 8A = - 18 B    :( -2)
4A = 9 B
4 * (3B - 3) = 9 B
12B - 12 = 9 B 
3 B = 12
B = 12/3
B = 4
A = 3 * 4 - 3
A = 12 - 3
A = 9


2 5 2